2004
DOI: 10.2337/diacare.27.6.1405
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Resting Energy Expenditure Considering Effects of Race and Diabetes Status

Abstract: OBJECTIVE -To evaluate the impact of diabetes status and race, in addition to other covariables, on the estimation of resting energy expenditure (REE).RESEARCH DESIGN AND METHODS -Demographic, anthropometric, and clinical parameters were assessed in 166 adults of varying weights. Subjects were categorized by race (white versus black) and into three subgroups based on glucose tolerance (normoglycemia, impaired glucose tolerance, and type 2 diabetes), termed the diabetes status index (DSI). REE was measured by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 42 publications
6
66
0
4
Order By: Relevance
“…Furthermore, REE was correctly predicted by the equations of the WHO (World Health Organisation, 1985) and Martin et al (2004), and differed by only 3·9 % from the value given by Huang et al (2004).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, REE was correctly predicted by the equations of the WHO (World Health Organisation, 1985) and Martin et al (2004), and differed by only 3·9 % from the value given by Huang et al (2004).…”
Section: Discussionmentioning
confidence: 80%
“…A number of studies have cited a relationship between glycaemic level or tolerance and REE (Gougeon et al 2002;Huang et al 2004;Martin et al 2004). These studies concern, first, values adjusted for differences in body composition, age, sex and race, and second, patients with uncontrolled diabetes (HbA 1c $ 8 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not unexpected because numerous studies have shown that REE among AA is lower than among C [9,19,20]. Furthermore, the validity of the Harris Benedict formula was determined in a population composed largely of C subjects.…”
Section: Discussionmentioning
confidence: 59%
“…REE has been shown to be lower among African American (AA) vs Caucasian (C) women [6,7], in part due to a lower amount of highly metabolically-active, trunk lean tissue mass [3,8]. However, REE among AA remained lower than among C by an average of 135 kilocalorie (kcal/d) even after adjusting for differences in lean body mass [9], suggesting that ethnicity is associated with an unidentified factor that affects REE. These findings suggest that the HB formula, which was validated in a study population largely comprised of C individuals, may overestimate REE in AA.…”
Section: Introductionmentioning
confidence: 99%